Comparison of Umbilical Cord Arterial Blood Gas and Neonatal Outcomes in Women with and without Meconium-Stained Amniotic Fluid During Labor - Mousavi, Sanaz; Akhgari, Aisan; Dehghan, Mahshid; Hoseinzadeh, Maryam; Mirghafourvand, Mojgan; Tafreshi, Rosa; Nikniaz, Leila (Current Women's Health Reviews, 2023)
Introduction: Meconium-stained amniotic fluid (MSAF) may increase maternal and neonatal complications. The favorable mode of delivery is controversial in women with MSAF. This study aimed to compare umbilical cord arterial blood gas (ABG) and neonatal outcomes in deliveries complicated by meconium and clear amniotic fluid during the active phase of labor. Materials and Methods: This observational study was performed on 144 term pregnant women (72 with MSAF and 72 with clear amniotic fluid) during the active phase of labor with ruptured membranes admitted to Al-Zahra and Taleghani hospitals in Tabriz, Iran, from June 2019 to June 2020. A checklist was used to record the ABG and neonatal outcomes. Results: The frequency of cesarean delivery in the MSAF group (25%) was significantly higher than in the women with clear amniotic fluid (20%) (P = 0.006). There was no statistically significant difference between the groups regarding pH, base excess, PCO2, 1- and 5- minute Apgar scores, and neonatal intensive care unit (NICU) admission of the newborn due to MSAF (P> 0.05). There was no incidence of hypoxic-ischemic encephalopathy, sepsis, and seizure. Conclusion: Given the non-significant difference between two groups of women with and without MSAF during labor in terms of neonatal outcomes and umbilical cord ABG, it seems that MSAF alone is not an indication for cesarean delivery. Thus, vaginal delivery is recommended in pregnant women with MSAF.
Keywords: umbilical cord arterial blood gas (ABG)